Caracterização da alvenaria estrutural de alta resistência - Fortes, Ernesto Silva (2017)
The research presented in this thesis consists of four parts. The first part reports the structural masonry properties characterization, with focus on determine the influence of the grout compressive strength to the compressive strength of grouted masonry constructed with high strength concrete masonry units, and the study of a new material used as dry capping in strength testing. The second part consists on the characterization of the compressive strength of high strength concrete blocks masonry walls, varying the mortar laying over the units, and evaluating the result of assembling a less resistant masonry bond-beam in the middle of the wall. The third part investigates the capacity and behavior of high strength concrete block masonry under concentric and eccentric axial loads and, finally, the fourth part evaluates the behavior of masonry frames with door and window openings under lateral force (bracing panels). The masonry here researched are build with concrete blocks with varying strengths from 32 to 75 MPa referred to the section gross area. Important information on the behavior of high strength masonry is reported from testing of 48 hollow and 162 grouted prisms, tested under axial compression. In addition, 36 mortar specimens, 162 grout sample and 18 blocos to determine the respective compressive strengths. A total of 474 high strength concrete blocks were tested to evaluate the use of dry capping materials to determine the compressive strength of concrete masonry units. In order to characterize the behavior of high strength masonry walls, thirty masonry walls, including hollow masonry and grouted, with and without a bond beam in the middle of the wall, and face shell and full-bed mortar joint, were tested under compression load. It was found that prism/unit ratio strength varies according to the block strength; the procedure of laying blocks with face shell-bed mortar joint is suitable for high strength concrete blocks, the value of wall: prism strength ratio of 0.7 can be adopted for high strength concrete blocks. The modulus of elasticity for masonry constructed with high strength blocos can be conservatively expressed as Em = 600 f´m, with no upper limits, as currently recommended for normal strength masonry by masonry design codes. Masonry walls are common structural members that typically resist compressive loads. Thus, a large number of such members are also required to resist combined axial load and bending, whether due to wind earthquake, or eccentricity of the axial compressive load. Therefore, seventy-two masonry prisms were constructed and tested under to evaluate the capacity and behavior of high strength structural masonry subject to compressive concentric and eccentric loading; both grouted and hollow prisms were considered. The results indicated that the load capacity of the prisms increases with increasing block strength; for prisms tested under eccentric loading, ultimate strain and ultimate stress at the extreme compressive fiber are larger than those of concentrically loaded specimens; the reduction in load capacity due to eccentric loading is more significant for grouted masonry than for their hollow counterparts; analysis of the results further, the flexural strength is 1.6 and 3 times higher than the axial strength for hollow and grouted masonry, respectively. And finally, in the experimental program developed at Brigham Young University jointly with the Unversity of Calgary, nine wall-assemblies, partially grouted and with opening were half-scale built and tested. The walls were subjected to cyclic lateral loading applied at the top of the wall through a reinforced concrete beam. It has been observed that the strength capacity of partially grouted walls with opening is similar in all cases tested, either the walls coupled with reinforced masonry beam or reinforced concrete beam, walls with door or window opening. For both cases of coupling, reinforced masonry beam and reinforced concrete beam, the wall-assemble behaves as a frame. No significant differences were observed in average lateral displacement and maximum lateral load, when coupling the walls with masonry beam or with reinforced concrete beams.